An experimental investigation on hot-wire anemometry measurements of collared-jets - Syed Abdul Fattah Alsagoff. (2012)
This report will report upon the effects of collared nozzles on jet flow fields. A variety of collared-jets will be studied thorough out this experiment, namely circular, square and triangular collared-jets. Results presented will include velocity profiles along the streamwise and the cross stream axis of the collared-jets. Data will be obtained through hot-wire anemometry. Step by step experimental procedures, data tabulation, data analysis of the experimental data, as well as the design and commissioning of the experimental rig will be included in this report.